Motility - finding a way to mobility attitude and behavior - Kjærulff, Aslak Aamot (Proceedings from the Annual Transport Conference at Aalborg University, 2011)
This paper presents the notion of motility as a way of understanding individual attitude and behavior in relation to mobility. Motility provides an elaborate understanding of the premises for individual mobility, and opens up for a conceptual analysis of mobility management policies. The aim of this analysis is to specify how this policy area aims at delivering changes within the attitude and behavior of travelers. Matching the theoretical notion of motility with a general characterization of mobility management policies show, that these theoretical perspectives could be a useful inclusion in the further work on mobility management policies in Denmark.